Sistem Informasi Laporan Keuangan Laba Rugi Berbasis Resep (Studi Kasus Food and Baverages Hotel XYZ) - Andika Tegar Setiawan; Irna Yuniar; Asti Widayanti (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2022)
Recipe standards are determined by the hotel to ensure that the manufacture of food menus produces standard quality. The preparation of this standard recipe often only considers the composition of the ingredients without considering the cost, so there are often problems where the costs set at the beginning do not match the costs incurred. The purpose of the research is to create an application that can calculate food cost planning by considering recipe standards so that users can evaluate in advance the costs that must be incurred when planning the manufacture of the product or selling the product. The application development method is made web-based with object-oriented techniques with a system development model using the Prototyping model. The company's business processes are designed using business process modeling created in the Business Process Model and Notation (BPMN). The application design uses the Unified Modeling Language (UML), namely the design of use case diagrams and the design of database structures using Entity Relationship Diagrams (ERD). The application is designed using the Hypertext Preprocessor programming language or commonly called PHP based on the CodeIgniter Framework and database management using MySQL. The result of this research is the application of a financial statement information system for food and beverage hotel income based on standard recipes. The results show that the application can determine recipe standards, calculate cost planning according to recipe standards, calculate total food costs, make purchases of raw materials based on cost planning and product sales transactions.